(Not so) Great Expectations: Listening to Foreign-Accented Speech Reduces the Brain’s Anticipatory Processes - Schiller, Niels O.; Boutonnet, Bastien P.-A.; De Heer Kloots, Marianne L. S.; Meelen, Marieke; Ruijgrok, Bobby; Cheng, Lisa L.-S. (Frontiers in Psychology, 2020)
This study examines the effect of foreign-accented speech on the predictive ability of our brain. Listeners actively anticipate upcoming linguistic information in the speech signal so as to facilitate and reduce processing load. However, it is unclear whether or not listeners also do this when they are exposed to speech from non-native speakers. In the present study, we exposed native Dutch listeners to sentences produced by native and non-native speakers while measuring their brain activity using electroencephalography. We found that listeners' brain activity differed depending on whether they listened to native or non-native speech. However, participants’ overall performance as measured by word recall rate was unaffected. We discussed the results in relation to previous findings as well as the automaticity of anticipation.